EBV-associated lymphoadenopathy in a child - H.B. Mateiko; U.A. Hlushko; T.V. Nesterova; L.V. Antoniuk; N.B. Horbal (Medičnì Perspektivi)
Lymphadenopathy is observed in 55% of children under  the age of 10 years and the most often it has a bacterial or viral etiology, but it also can manifest as lymphoproliferative diseases or lymphomas. Lymphoproliferative diseases are characterized by uncontrolled growth of lymphocytes with the development of monoclonal lymphocytosis, lymphadenopathy and bone marrow infiltration. Since the Epstein-Barr virus (EBV) has oncogenic potential, it is essential for doctors to be vigilant about generalized persistent lymphadenopathy on the background of chronic persistent Epstein-Barr infection. The purpose of the article is to increase the awareness of doctors of various specialties about the risk of developing EBV-associated lymphoproliferative diseases in children with generalized persistent lymphadenopathy using the example of a clinical case discussion. The article describes a clinical case of a 14-year-old patient with persistent lymphadenopathy on the background of chronic Epstein-Barr infection. Immunohistochemical study of the lymph node biopsy revealed reactive hyperplasia with expressed immune blast transformation, the presence of CD30-positive cells while excluding Hodgkin lymphoma. It is recommended to involve a multidisciplinary team to prescribe appropriate antiviral therapy, regularly monitor the clinical course, dynamics of laboratory and immunological indicators. The result of the study is the recommendation to repeat biopsy in the absence of positive dynamics in patients with persistent Epstein-Barr infection and lymphadenopathy.